2006
DOI: 10.4028/www.scientific.net/msf.524-525.479
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Influence of a Trailing Heat Sink on the Welding Residual Stress Distribution

Abstract: It has been shown that the introduction of a trailing heat sink following a welding heat source at a short distance can reduce or even eliminate the buckling deformation of welded thin plate structures. To increase the insight into the stress development during welding with a trailing heat sink, residual stress measurements were carried out by means of laboratory X-ray and synchrotron X-ray diffraction techniques. Both the laboratory X-ray and the synchrotron X-ray experiments show a difference between the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 4 publications
(6 reference statements)
0
13
0
Order By: Relevance
“…303 Michaleris and Sun 304 and Dull et al 305 have applied thermal tensioning to reduce buckling distortion, whereas Dong et al 306 developed an in-process thermal stretching technique for effective mitigation of residual stresses and distortion on repair welding of aluminium panels. Barber et al, 307 van der Aa et al 308 and Williams and co-workers 285,[309][310][311] have applied local cooling to FSW, using either solid or liquid CO 2 trailing the heat source, as a means of creating dynamically controlled low residual stress and distortion free welds; others have used water jets. 312 Several mechanical tensioning systems have been proposed.…”
Section: As Welded Residual Stressesmentioning
confidence: 99%
“…303 Michaleris and Sun 304 and Dull et al 305 have applied thermal tensioning to reduce buckling distortion, whereas Dong et al 306 developed an in-process thermal stretching technique for effective mitigation of residual stresses and distortion on repair welding of aluminium panels. Barber et al, 307 van der Aa et al 308 and Williams and co-workers 285,[309][310][311] have applied local cooling to FSW, using either solid or liquid CO 2 trailing the heat source, as a means of creating dynamically controlled low residual stress and distortion free welds; others have used water jets. 312 Several mechanical tensioning systems have been proposed.…”
Section: As Welded Residual Stressesmentioning
confidence: 99%
“…Michaleris and Sun [11] and Dull et al [12] have applied thermal tensioning to reduce buckling distortion, whilst Dong et al [13] developed an in-process thermal-stretching technique for effectively mitigating residual stresses and distortion on repair welding of aluminium panels. In addition, Barber et al [14], van der Aa et al [15] and Williams and co-workers [16], have applied local cooling, with either solid or liquid CO 2 trailing the heat source, as a means of creating dynamically controlled low residual stress and distortion free welds. Several mechanical tensioning systems have also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Li et al and van der Aa et al have looked into the positioning of heat sinks in DC-LSND and found it to be the most important factors for maximising the relief of residual welding stresses. 18,33 Richards et al found that a leading heat sink was much less effective in modifying the thermal field and reducing the residual stresses. In order to enhance the controlling efficacy, the heat sink should be placed behind the stir tool as a trailing heat sink.…”
Section: Discussionmentioning
confidence: 99%
“…If the heat sink was placed too far behind the heat source, then the controlling effect could be reduced. 18,33 The time when the material is hot enough for the cold sink to affect it depends on the material's flow stress with temperature. The flow stress needs to be very low for tensioning to work.…”
Section: Discussionmentioning
confidence: 99%